Determination of Copper, Iron, Manganese, Nickel and Zinc in Tea Leaf Consumed in Syria by Flame Atomic Absorption Spectrometry after Microwave Digestion - Antakli, Saad; Sarkis, Nazira; Mahmod Al-Check, Ahmad (Asian Journal of Chemistry, 2011)
The present work describes tea leave microwave digestion procedure by using new acid mixture (nitric acid and perchloric acid) for determining copper, iron, manganese, nickel and zinc in tea samples, employing flame atomic absorption spectrometry (FAAS). The optimization conditions involving the experiment factors: tea sample amount, microwave power and power time were studied for some kinds of tea consumed in Syria. The relative standard deviations of the method were found below 5 % for the 5 elements. The proposed method was used for the determination of the five elements in tea leave consumed in Syria for 39 tea samples. The obtained concentration of copper, iron, manganese, nickel and zinc varied between 10.6-54.4, 74.8-854.9, 225.1-1633.1, 1.1-16.3 and 18.0-44.2 (μg/g), respectively. These metals were also determined in tea infusion in boiled distilled water during (2-30 min) for three different samples. The percentage of the element contents in the infusion related to the total amount in tea leave were: zinc 19.71-28.34 %, manganese 11.79-26.95 %, iron < 5 %, copper and nickel were below the detection limit.